Increased natural killer cell subsets with inhibitory cytokines and inhibitory surface receptors in patients with recurrent miscarriage and decreased or normal subsets in kidney transplant recipients late post‐transplant. (31st May 2018) - Zhu, L.; Aly, M.; Wang, H.; Karakizlis, H.; Weimer, R.; Morath, C.; Kuon, R. J.; Toth, B.; Ekpoom, N.; Opelz, G.; Daniel, V.
Summary: Patients with recurrent miscarriage (RM) show up‐regulated cytotoxic natural killer (NK) cells that are suspected to play a causal role in abortion. In the present study, we investigated counter‐regulating inhibitory mechanisms and compared the results in RM patients with those of healthy controls (HC), patients with end‐stage renal disease (ESRD) and kidney transplant recipients late post‐transplant (TX). NK, NK T and T cell subsets were analysed in the peripheral blood of 31 RM, 14 female ESRD and nine female TX patients as well as 21 female HC using eight‐colour fluorescence flow cytometry. Compared with HC, RM patients showed significantly higher absolute numbers of CD56 + NK cells co‐expressing the phenotype interferon (IFN)‐γR +, IL‐4 +, transforming growth factor (TGF)‐β +, IL‐4 + human leucocyte antigen D‐related (HLA‐DR) +, TGF‐β + HLA‐DR +, IL‐4 + TGF‐β +, IL‐4 + TGF‐β –, IFN‐γ + and/or IL‐10 – IFN‐γ + (all P ≤ 0·01), more IL‐17 + CD56 bright ( P = 0·028) NK cells and more CD56 dim CD16 + NK cells co‐expressing IFN‐γR, IFN‐γ, IL‐4 and/or TGF‐β (all P ≤ 0·01). When the same cell subsets were analysed in ESRD or TX patients, cytokine‐producing NK cell subsets were not significantly different from those of HC. RM patients showed significantly higher absolute numbers of CD158a +, CD158b +, CD158a – CD158e + (all P < 0·05), NKG2D + NKG2A +, NKG2D + NKG2A –, NKG2D + and/or NKG2A + (all P ≤ 0·01) CD56 + NK cells and higher CD158a +, CD158b + (all P < 0·05), NKG2D + and/or NKG2A + (all P < 0·01) CD56 dim+ CD16 + NK cells than HC. In contrast, ESRD patients had normal and TX recipients had lower CD158a + and NKG2D + NKG2A – CD56 + NK cells and lower CD158a + CD56 dim+ CD16 + NK cells (all P < 0·05) than HC. RM patients have abnormally high circulating NK cells expressing inhibitory cytokines and inhibitory surface receptors which might contribute to the pathogenesis of RM. Abstract : Our data show that compared to female healthy controls, recurrent miscarriage patients have abnormally high NK, NKT and T cells in the blood which express inhibitory cytokines and inhibitory surface receptors. In contrast, dialysis and transplant patients had normal or even decreased levels of these cell subsets. We interpret these results as showing that the upregulation of inhibitory mechanisms in recurrent miscarriage patients represents a counter regulation to a strongly upregulated cytotoxic immune system, possibly the cause of recurrent miscarriage.